Trace element nutrition in the tropical zebu cattle type. Lessons from the Gilgel Gibe catchment, Ethiopia - Dermauw, Veronique (Afrika Focus, 2014)
In the tropics, cattle are majorly dependent on natural pastures growing on poor soils and as a result prone to trace element deficiencies. This work investigated several aspects of trace element nutrition in zebu (Bos indicus) cattle, the most widely used cattle type in the tropics. Through several trials conducted at the Gilgel Gibe catchment, Ethiopia, we aimed to study factors influencing the flow of trace elements from soil to plant and grazing zebu cattle, and to investigate the impact of trace element status on health, production and trace elements in animal products. Overall, trace element, e.g., Cu, deficiencies were widely prevalent. Environment and certain grazing strategies were intimately related and affected trace element supply whereas cattle type affected trace element status. The effect of trace element status on trace elements in animal products was obvious, whereas the impact on health and production was less clear-cut. Key words: trace elements, minerals, cattle, zebu, Bos indicus, Ethiopia, tropics